Characterization of cellulose structure of Populus plants modified in candidate cellulose biosynthesis genes. (November 2016) - Bali, Garima; Khunsupat, Ratayakorn; Akinosho, Hannah; Payyavula, Raja S.; Samuel, Reichel; Tuskan, Gerald A.; Kalluri, Udaya C.; Ragauskas, Arthur J.
Abstract: The recalcitrant nature of lignocellulosic biomass is a combined effect of several factors such as high crystallinity and high degree of polymerization of cellulose, lignin content and structure, and the available surface area for enzymatic degradation (i.e., accessibility). Genetic improvement of feedstock cell wall properties is a path to reducing recalcitrance of lignocellulosic biomass and improving conversion to various biofuels. An advanced understanding of the cellulose biosynthesis pathway is essential to precisely modify cellulose properties of plant cell walls. Here we report on the impact of modified expression of candidate cellulose biosynthesis pathway genes on the ultra-structure of cellulose, a key carbohydrate polymer of Populus cell wall using advanced nuclear magnetic resonance approaches. Noteworthy changes were observed in the cell wall characteristics of downregulated KORRIGAN 1 (KOR) and KOR 2 transgenic plants in comparison to the wild-type control. It was observed that all of the transgenic lines showed variation in cellulose ultrastructure, increase in cellulose crystallinity and decrease in the cellulose degree of polymerization. Additionally, the properties of cellulose allomorph abundance and accessibility were found to be variable. Application of such cellulose characterization techniques beyond the traditional measurement of cellulose abundance to comprehensive studies of cellulose properties in larger transgenic and naturally variable populations is expected to provide deeper insights into the complex nature of lignocellulosic material, which can significantly contribute to the development of precisely tailored plants for enhanced biofuels production. Graphical abstract: Highlights: Characterized impact of modified expression of cellulose biosynthesis pathway genes on cellulose. Transgenic lines showed variation in cellulose ultrastructure and degree of polymerization. Transgenic lines exhibited differences in cellulose allomorph abundance and accessibility.